Watsonia vicschuettei (Iridaceae, Watsonieae), a replacement name for the illegitimate Watsonia palustris - Potgieter, Christina Johanna; Johnson, Isabel Marion (Phytotaxa, 2018)
A newly discovered South African species of Watsonia Miller (1758: 184), family Iridaceae Jussieu (1789: 57), was described as Watsonia palustris Goldblatt & Manning (2016: 151). During the process of digitizing Watsonia holdings in the Bews Herbarium (NU) we realised that this name is illegitimate according to Art. 53.1 of the ICN (McNeill et al. 2012). Watsonia palustris Goldblatt & J.C.Manning is a later homonym of W. palustris Persoon (1805:43), in itself a superfluous name for Dierama pendulum (Linnaeus f. 1781: 91) Baker (1877: 99). We present a replacement name for this taxon here.